Rebuking the Spirit a New Analysis of the Lazarus Story of John 11 - Lindars, Barnabas (New Testament studies, 1992)
The story of the raising of Lazarus (John 11.1–44) is one of the most dramatic and impressive of the compositions in the Fourth Gospel. For this very reason it raises a host of problems for the biblical critic. There can be no dispute that it has a theological purpose which dominates the whole narrative. This is clearly set out in the first words attributed to Jesus: ‘This illness is not unto death; it is for the glory of God, so that the Son of God may be glorified by means of it’ (v. 4). The same point is referred to again just before the climax of the narrative in v. 40. But the more prominent the theological aim, the more difficult it becomes to view the narrative simply in terms of history. It must surely be the case that John has based his composition on a source, which was probably much simpler and briefer than the splendid story which it has become in his hands. But the source must be reconstructed before we can begin to think of it in historical terms. The modern tendency is to give up such attempts as hopeless, and to concentrate on the meaning of the text as it stands. But even that presents pitfalls to the critic. All seems well until we come to v. 33: ‘Jesus…was deeply moved in spirit (ένεβριμήσατο τῷ πνεύματι) and troubled.’ Unfortunately the Greek words do not mean ‘deeply moved in spirit’ (RSV). In his recent commentary on John in the Word Biblical Commentary, G. R. Beasley-Murray marshalls a great array of evidence to show that the meaning must be ‘became angry in spirit’. But why should Jesus be represented by John as angry? The effort to answer this question affects the interpretation of the whole story.